Facilities Development And Socialization Of Bule-Brazilians In Buckets (Guide For The Event Of Community Economic Independence) - Efta Dhartikasari Priyana; Said Salim Dahda; Wisda Mulyasari; Dzakiyah Widyaningrum; Moh. Dian Kurniawan; Khoirul Aman Makhrudy (INNOVATION RESEARCH JOURNAL, 2021)
Gresik, one of the industrial cities in Indonesia, has recorded that more than 1000 workers have been laid off. The increasing unemployment in Gresik makes the government have to work extra hard to help the community's problems. However, the burden of this community's powerlessness cannot be transferred to the government all the time. Even though the government is still very busy with the unresolved COVID-19 cases. The Community Service proposed by the UMG Industrial Engineering team took the theme of Fish Cultivation in Buckets (Fish farming in buckets), which is better known as aquaponics. The concept of Fish farming in buckets itself is to unite plants and fish in a bucket, resulting in a symbiotic mutualism that is very beneficial for both parties. The object of this research will be conducted at the Industrial Engineering Study Program, University of Muhammadiyah Gresik (TI-UMG) by giving invitations to residents of Yosowilangun Gresik, especially the FAMILY WELFARE DEVELOPMENT group and the Yatim Mandiri foundation. The reason why the debriefing is preferred to the FAMILY WELFARE DEVELOPMENT and Yatim Mandiri groups is none other than the fact that FAMILY WELFARE DEVELOPMENT is a collection of housewives where it is likely that some of the heads of their families will be laid off. And the Yatim Mandiri Foundation is here to support the improvement of the economic independence of the orphan group.